The development of coordination abilities at a stage of the previous basic preparation in sports dances - Ivan Ivanov (Слобожанський науково-спортивний вісник, 2015)
Purpose: to prove a technique of the improvement of special physical fitness due to the development of coordination abilities at a stage of the previous basic preparation. Material and Methods: theoretical analysis and synthesis of data of scientifically methodical literature and empirical materials of the scientific research, pedagogical methods of the research, tool methods: program of diagnostics of the development of psychophysiological abilities (APC "Sports psychophysiologist"), methods of mathematical statistics. Results: the technique is developed which includes means of the general physical preparation, the specially developed complexes of danced-jumped exercises, the dancing combinations and means which are picked up taking into account the leading motive, functional abilities and special technical characteristics of movements and also has a strictly certain sequence of the realization of means during each cycle of classes. Conclusions: the application of the experimental technique of the improvement of special physical fitness of sportsman in the training process led to the improvement and enhancement of their technical preparedness and the increase of the competitive productivity of their performances